Profit Sharing and Peer Reporting - Jeffrey P. Carpenter; Andrea Robbett; Prottoy Akbar (Institute for the Study of Labor (IZA), 2016)
Despite the "1/N problem" associated with profit sharing, the empirical literature finds that sharing profits with workers has a positive impact on work team and firm performance. We examine one possible resolution to this puzzle by observing that, although the incentive to work harder under profit sharing is weak, it might be sufficient to motivate workers to report each other for shirking, especially if the workers are reciprocally-minded. Our model provides the rationale for this conjecture and we discuss the results of an experiment that confirms that profit sharing is most effective when peer reporting is possible.
Keywords: C92; J30; D20; M52; 330; team production; profit sharing; peer reporting; reciprocity; experiment